1999
DOI: 10.1557/s1092578300003550
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Crystalline Quality of Group III Nitrides on Sapphire Using Low Temperature Interlayers

Abstract: In organometallic vapor phase epitaxial growth of group III nitrides on sapphire, insertion of a low temperature interlayer is found to improve crystalline quality of AlxGa1−xN layer with x from 0 to 1. Here the effects of the low temperature deposited GaN or AlN interlayers on the structural quality of group III nitrides is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…by HVPE, many methods are known to reduce the dislocation density and the most often applied are based on masking and lateral overgrowth commonly known as ELOG or LEO [10] and pendeo epitaxy [11,12], all methods involving an ex-situ processing step before growth or after a first buffer layer has been grown. In-situ methods as Al(Ga)N/GaN superlattices [13] or AlN or Si x N y interlayers [14,15] are also suited to reduce the dislocation density without ex-situ processing. Table 1) does, as opposite to GaN on sapphire, induce tensile stress in GaN on silicon resulting in crack formation when cooling.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…by HVPE, many methods are known to reduce the dislocation density and the most often applied are based on masking and lateral overgrowth commonly known as ELOG or LEO [10] and pendeo epitaxy [11,12], all methods involving an ex-situ processing step before growth or after a first buffer layer has been grown. In-situ methods as Al(Ga)N/GaN superlattices [13] or AlN or Si x N y interlayers [14,15] are also suited to reduce the dislocation density without ex-situ processing. Table 1) does, as opposite to GaN on sapphire, induce tensile stress in GaN on silicon resulting in crack formation when cooling.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…These cracks, observable in an optical microscope on a ~ mm scale, have been reported to have a potentially dual role in the strain relaxation, through the formation of misfit dislocation on the basal plane [2] in addition to the relaxation caused by the crack itself. Such crack networks can be avoided through the use of a low temperature interlayer of AlN at the AlGaN-GaN interface for example [4], but these methods are not suitable in all cases and can cause an increased threading dislocation density.The above studies have discussed the propagation and relaxation induced by cracks, but none have reported on their nucleation or on the microscopic structural properties for layers below which the gross cracks have been observed. In a previous report [5] we have suggested that the gross cracks may be formed as a result of "microcracks" observed at much lower thicknesses.…”
mentioning
confidence: 99%
“…This isolation layer acts either as a trap for possible oxygen contamination, or as a layer that interrupts the highly defective layer near the GaN/sapphire interface. Such isolation layer can also improve the crystalline quality of the sample [14].…”
Section: Discussionmentioning
confidence: 99%